Transduction of human T cells with a novel T-cell receptor confers anti-HCV reactivity. - Yi Zhang; Yeuying Liu; Kelly M Moxley; Lucy Golden-Mason; Lucy Golden-Mason; Michael G Hughes; Tongxin Liu; Mirjam H M Heemskerk; Hugo R Rosen; Michael I Nishimura (PLoS Pathogens)
Hepatitis C Virus (HCV) is a major public health concern, with no effective vaccines currently available and 3% of the world's population being infected. Despite the existence of both B- and T-cell immunity in HCV-infected patients, chronic viral infection and HCV-related malignancies progress. Here we report the identification of a novel HCV TCR from an HLA-A2-restricted, HCV NS3:1073-1081-reactive CTL clone isolated from a patient with chronic HCV infection. We characterized this HCV TCR by expressing it in human T cells and analyzed the function of the resulting HCV TCR-transduced cells. Our results indicate that both the HCV TCR-transduced CD4(+) and CD8(+) T cells recognized the HCV NS3:1073-1081 peptide-loaded targets and HCV(+) hepatocellular carcinoma cells (HCC) in a polyfunctional manner with cytokine (IFN-gamma, IL-2, and TNF-alpha) production as well as cytotoxicity. Tumor cell recognition by HCV TCR transduced CD8(-) Jurkat cells and CD4(+) PBL-derived T cells indicated this TCR was CD8-independent, a property consistent with other high affinity TCRs. HCV TCR-transduced T cells may be promising for the treatment of patients with chronic HCV infections.